2015
DOI: 10.4172/2155-9597.1000251
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Study of Post-Operative Wound Infections in a Tertiary Care Hospital

Abstract: Out of 800 patients admitted for surgery 116 (14.5%) suffered from wound infections. Of these, 57 out of 277 (20.58%) were emergency surgery patients and 59 out of 523 (11.28%) were elective surgery. The infection rate was 32.2% in dirty wounds followed by 29.22% in contaminated wounds, 9.0% in clean-contaminated and 3.85% in clean wounds. There were significantly more infections in wounds with drains (21.79%) than without drains (10.37%) P<0.01). Only 8.37% with pre-operative antibiotic prophylaxis developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
4
6
2
Order By: Relevance
“…The frequency of isolates of Staphylococcus aureus from infected surgical wounds reported by other researchers was in the range of 19-75%. 11,14,15,19,20 Enterococcus species Among catalase negative organisms, 6.2% were Enterococci in the present study while that reported by other authors ranged from 0.06-7.1%. 13,14,19 β haemolytic Streptococci Streptococcus spp was isolated from 3 cases (Table 1).…”
Section: Staphylococcus Speciescontrasting
confidence: 54%
See 4 more Smart Citations
“…The frequency of isolates of Staphylococcus aureus from infected surgical wounds reported by other researchers was in the range of 19-75%. 11,14,15,19,20 Enterococcus species Among catalase negative organisms, 6.2% were Enterococci in the present study while that reported by other authors ranged from 0.06-7.1%. 13,14,19 β haemolytic Streptococci Streptococcus spp was isolated from 3 cases (Table 1).…”
Section: Staphylococcus Speciescontrasting
confidence: 54%
“…4,11,14,15 The present study showed 7.6% of isolates were that of Citrobacter spp (12 C. freundii and 4 C. diversus). Other studies from Nagpur and New Delhi have reported frequencies of 2.27% and 4.1%, respectively.…”
Section: Enterobacteriaciaementioning
confidence: 94%
See 3 more Smart Citations